BJHP – Building on our strengths - Alison Wearden; David French (British Journal of Health Psychology, 2013)
Objectives Individuals with visible differences often experience appearance-related stigma and discrimination, reinforced by negative media portrayals. In contrast, positive portrayals may challenge stereotypes and promote acceptance. This study examined whether exposure to positive, negative or neutral images of visible difference influences appearance-related stigma, body appreciation and broad conceptualizations of beauty. It was hypothesized that positive images would decrease stigma and increase body appreciation and broad conceptualizations of beauty, whereas negative images would increase stigma and reduce broad conceptualizations of beauty. Design An online randomized controlled experiment using a mixed repeated-measures design compared three conditions (positive, negative, neutral) across pre- and post-exposure. Methods A sample of 103 adults viewed 10 images of individuals with visible differences presented in one of three conditions: positive (positive captions), negative (villains with visible differences and negative captions) or neutral (without captions). Participants completed pre- and post-measures of appearance-related stigma, body appreciation and broad conceptualizations of beauty. Repeated-measures ANOVAs examined within- and between-group changes. Results Appearance-related stigma significantly increased in the negative condition, while remaining unchanged in the positive and neutral groups. Body appreciation significantly increased from pre- to post- across all conditions. No significant effects emerged for broad conceptualizations of beauty. Conclusions Negative portrayals of visible difference may reinforce stigma, highlighting the need to discourage such depictions in media. While positive exposure did not significantly reduce stigma, viewing images of visible difference increased observers' body appreciation, indicating potential downward social comparison. Future research should explore strategies to strengthen stigma reduction and broaden conceptualizations of beauty.